Drop-on-demand printing of amine-responsive fluorescence-ratiometric sensor array for online monitoring meat freshness - Zhijian Wang; Xudong Shi; Jingze Guo; Lin Wang; Meilin Cao; Shiyao Wang; Yisheng Chen (Food Chemistry: X)
Aiming to enable online freshness-monitoring of meat within modified-atmosphere package, we developed a ratiometric array that was fluorescently responsive to volatile organic compounds-ammonia (NH3) released by protein decaying. The array was consisted of two 3 mm × 6 mm rectangles precisely and uniformly printed with fluorescein isothiocyanate (FITC) as indicator and rhodamine B (RhB) as internal reference on the filter-paper, respectively. The fluorescence intensity of the array area was calibrated according to Green/Red ratio of the digitalized pixels extracted from images facilitated by a smartphone. The fluorescence-ratiometric sensor array displayed remarkable detection performances, including high sensitivity (LOD = 1.1 ppm), stability (91 % responding attenuation over 10 d of storage) and reproducibility (RSD < 10 %), which was further validated with real pork and shrimp samples. Subsequently, the fluorescent signals of the dual-rectangle array showed high correlation to the total volatile base nitrogen value that was officially used for indexing the meat freshness status.